INDUSTRIAL MODERNIZATION OF THE UKRAINIAN SSR AT THE MICRO LEVEL: THE DEVELOPMENT OF THE DARNYTSIA CHEMICAL – PHARMACEUTICAL PLANT IN THE 1950s – 1960s - Podat, Roman (Young Scholars Grinchenko – Seton International Journal, 2026)
This paper examines industrial modernization in the Ukrainian SSR through the case of the Darnytsia Chemical-Pharmaceutical Plant in the 1950s – 1960s. Based on annual financial reports, construction materials, and trade-union protocols from enterprise archives, it reconstructs the plant’s transformation from a postwar branch of a research institute into a large pharmaceutical enterprise. The study argues that micro-level modernization was contradictory: growth in output, mechanization, and product range coexisted with dependence on imported technology, chronic planning distortions, and difficult working conditions.